PERLINDUGAN HAK-KESEHATAN DAN HAK EKONOMI MASYARAKAT HUKUM ADAT DI PERBATASAN KALIMANTAN UTARA DALAM STATUS KEDARURATAN KESEHATAN AKIBAT PANDEMI COVID-19 - Salinding, Marthen B. (Lex Journal: Kajian Hukum & Keadilan, 2021)
Protection of health rights and economic rights for the legal community at the time of the Covid-19 pandemic was carried out simultaneously, there cannot be rights that take precedence and leave other rights ... Prioritizing the fulfillment of health rights and ignoring economic rights has implications for the emergence of social insecurity, the opposite is true when prioritizing health rights. economic rights rather than health rights will threaten the safety of people's lives. This study aims to explain that the protection of the health rights and economic rights of indigenous peoples in the border area of ​​North Kalimantan must be carried out simultaneously and in balance. The research method used is a normative juridical research method. The results showed that the local government had provided protection for the health rights and economic rights of indigenous peoples in the border area of ​​North Kalimantan during the pandemic simultaneously and in balance. Keywords; Protection, economic rights, health rights of indigenous peoples